Association of sleep quality and nap duration with cognitive frailty among older adults living in nursing homes - Liu, Siyue; Hu, Zhao; Guo, Yicong; Zhou, Feixiang; Li, Shaojie; Xu, Huilan (Frontiers in Public Health, 2022)
Background: Sleep status, including sleep quality and nap duration, may be associated with frailty and cognitive impairment in older adults. Older adults living in nursing homes may be more prone to physical and cognitive frailty. This study aimed to investigate the association between sleep quality, nap duration, and cognitive frailty among older adults living in nursing homes. Methods: This study included 1,206 older adults aged ≥ 60 years from nursing homes in Hunan Province, China. A simple frailty questionnaire (FRAIL scale) and Mini-Mental State Examination were used to assess physical frailty and cognitive impairment, respectively, to confirm cognitive frailty. The Pittsburgh Sleep Quality Index was used to assess the sleep quality. Nap duration was classified as follows: no, short (≤30 min), and long (>30 min) napping. Multinomial logistic regression was used to estimate the odds ratio (OR) and 95% confidence interval (CI). Results: The prevalence of cognitive frailty among older adults in nursing homes was 17.5%. Approximately 60.9% of the older adults had poor sleep quality. Among the 1,206 participants, 43.9% were aged without napping, 29.1% had a short nap, and 26.9% had a long nap. After adjusting for all covariates, poor sleep quality (OR, 2.53; 95% CI, 1.78–3.59; P<0.001) and long nap duration (OR, 1.77; 95% CI, 1.19–2.64; P=0.003) were associated with higher odds of cognitive frailty, but short nap duration (OR, 0.60; 95% CI, 0.40–0.89; P=0.012) was associated with a low prevalence of cognitive frailty. Conclusion: Poor sleep quality and long nap duration are significantly associated with a high risk of cognitive frailty among older adults in nursing homes. Short nap duration was associated with a low prevalence of cognitive frailty. However, these associations require further validation in older adults. Registration: https://osf.io/57hv8